2018
DOI: 10.1016/j.foodres.2017.12.013
|View full text |Cite
|
Sign up to set email alerts
|

High isostatic pressure and thermal processing of açaí fruit (Euterpe oleracea Martius): Effect on pulp color and inactivation of peroxidase and polyphenol oxidase

Abstract: The present study evaluated the effect of high isostatic pressure (HIP) on the activity of peroxidase (POD) and polyphenol oxidase (PPO) from açaí. Açaí pulp was submitted to several combinations of pressure (400, 500, 600MPa), temperature (25 and 65°C) for 5 and 15min. The combined effect of HIP technology and high temperatures (690MPa by 2 and 5min at 80°C) was also investigated and compared to the conventional thermal treatment (85°C/1min). POD and PPO enzyme activity and instrumental color were examined af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 47 publications
0
20
0
5
Order By: Relevance
“…Many common and effective inhibitors of PPO (Holzwarth, Wittig, Carle, & Kammerer, 2013) such as ascorbic acid, citric acid, sodium sulfite, phytic acid, sodium chloride and other compounds that have thiol groups (L-cysteine, glutathione) have been reported. More recently, the characterization of PPO has been studied in various plants food such as mung bean sprouts (Sikora & Świeca, 2018), bayberry juice (Cao, Cai, Wang, & Zheng, 2017), acai fruit (Jesus, Leite, & Cristianini, 2018), blueberry (Siddiq & Dolan, 2017), tea leaf (Teng et al, 2017), soursop nectar (Anaya-Esparza et al, 2017), cape gooseberry (Bravo & Osorio, 2016). However, few detailed studies have reported on the purification and characterization of water yam PPO.…”
Section: Introductionmentioning
confidence: 99%
“…Many common and effective inhibitors of PPO (Holzwarth, Wittig, Carle, & Kammerer, 2013) such as ascorbic acid, citric acid, sodium sulfite, phytic acid, sodium chloride and other compounds that have thiol groups (L-cysteine, glutathione) have been reported. More recently, the characterization of PPO has been studied in various plants food such as mung bean sprouts (Sikora & Świeca, 2018), bayberry juice (Cao, Cai, Wang, & Zheng, 2017), acai fruit (Jesus, Leite, & Cristianini, 2018), blueberry (Siddiq & Dolan, 2017), tea leaf (Teng et al, 2017), soursop nectar (Anaya-Esparza et al, 2017), cape gooseberry (Bravo & Osorio, 2016). However, few detailed studies have reported on the purification and characterization of water yam PPO.…”
Section: Introductionmentioning
confidence: 99%
“…Polyphenol oxidase (PPO) is a major copper enzyme [ 2 ], also known as catechol oxidase, tyrosinase, and so forth [ 3 ], and is the most important deteriorative enzyme that accelerates oxidation and degradation of polyphenols and their derivatives [ 4 ]. PPO is located in the chloroplasts [ 5 , 6 ] and its activation takes places during cell-damaging treatment (e.g., slicing, cutting or pulping) where oxygen is available and the local pH is not too acidic [ 7 , 8 ], thus causing the formation of brown pigments [ 2 , 9 ]. In fact, the oxygen catalyzes the enzyme reaction where the monophenols forming o -diphenols (monophenolase activity) and then the oxidized substrate react, producing o -quinones (diphenolase activity) [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tyrosinase, catechol oxidase and laccases are the three types of PPO which catalyze hydroxylation of monophenols to diphenols (cresolase activity) and oxidation of diphenols to quinone (catecholase activity) that further polymerized to brown pigments called melanins (Simsek et al 2007;Queiroz et al 2008). PPO enzyme has been studied in many fruits and vegetables due to its significant role in browning process (Wuyts et al 2006;Anaya-Esparza et al 2017;Jesus et al 2018). Different studies have clearly shown that PPO enzyme is mostly involved in the enzymatic browning process of plant food that occurs during storage and processing (Munoa-pina et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The best studied role of PPO in bacteria is the melanins formation that provides protection to the spores of bacteria and cells against oxidants, UV radiations and free radicals (Claus and Decker 2006). In most recent studies PPO has been studied in many plant food such as mung bean sprouts (Sikora and Świeca, 2018) fruit (Jesus et al 2018) bayberry juice (Cao et al 2017), blueberry (Siddiq and Dolan, 2017), tea leaf (Teng et al 2017), and cape gooseberry (Bravo and Osorio, 2016). Banana is considered a significant crop in the whole world and one of the most important food sources in the developing world (Paul et al 2001).…”
Section: Introductionmentioning
confidence: 99%